Finding the Most Catalytically Active Platinum Clusters With Low Atomicity1. (15th July 2015) - Imaoka, Takane; Kitazawa, Hirokazu; Chun, Wang‐Jae; Yamamoto, Kimihisa
Abstract On a subnanometer scale, an only one‐atom difference in a metal cluster may cause significant transitions in the catalytic activity due to the electronic and geometric configurations. We now report the atomicity‐specific catalytic activity of platinum clusters with significantly small atomicity, especially below 20. The atomic coordination structure is completely different from that of the larger face‐centered cubic (fcc) nanocrystals. Here, an electrochemical study on such small clusters, in which the atomicity ranged between 12 and 20, revealed Pt19 as the most catalytically active species. In combination with a theoretical study, a common structure that leads to a high catalytic performance is proposed.